PERKEMBANGAN KESEJAHTERAAN RUMAH TANGGA TRANSMIGRAN DAERAH PANTAI Kabupaten Kulon Progo, Daerah Istimewa Yogyakarta - Antonia Sasap Abao; Nining Sofiati; Rita Dewi Tristianti (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2006)
The observation and interview with some transmigrants in Karangsewu and Bugel found that the rate of prosperity since they joined the transmigration program was not yet promising. They are some factors causing it, such as less commitment from the government in handling the program and problems inside it, the condition of the land given to the transmigrants were sandy land which is not good for agriculture, and the low quality of human resources itself. All that causing factors resulted in the low level of prosperity of those who joined the transmigration program. It showed in the classification of their family level which is still KS-1 (family with the first level of prosperity). The cata collected by doing quick survey through observation and indepth interview.